Pengaruh Pembelajaran Pendidikan Agama Islam Dan Budi Pekerti Terhadap Penguatan Karakter Siswa SMK Al-Qodiri Jember - Muhamad Ansori (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2023)
This study aims to determine whether there is an influence of Islamic Religious Education and Moral Education on students' character strengthening and to determine how much influence Islamic Religious Education has on students' character. This research uses a quantitative research type using associative methods. Source of data obtained in the form of primary data. The data collection technique is in the form of a questionnaire. The population in this study amounted to 362 respondents and the sample in this study amounted to 65 respondents using a sample replacement technique by means of simple random sampling. The data analysis process uses simple regression analysis, with Islamic Religious Education as the independent or independent variable and character as the dependent or dependent variable. Based on the results of research conducted by the author, the results of testing the hypothesis of Islamic Religious Education showed a tcount of 6.171 or positive with a significant level of 0.000. Then t count > t table (6.171 > 2.000) and a significant level of less than 0.05 (0.000 <0.05), which means that the hypothesis in this study rejects Ho and accepts Ha, meaning that there is a significant influence between Islamic Religious Education Learning and Budi Pekerti towards Strengthening student character. Through the results of the calculations that have been carried out to obtain a linear regression value Y = 14.688 + 0.661X, sig. Level 0.000 < 0.05 (alpha value), so the conclusion is that there is an influence between Islamic Religious Education and Moral Education Learning with Character Strengthening. Based on the output, the R2 value (R Square) is 0.377 (0.614 x 0.614) or 37.7%. Therefore it can be concluded that learning Islamic religious education has a significant influence on strengthening the character of students.